MASA DEPAN MADRASAH DALAM PERSPEKTIF KEPALA MADRASAH - Mutammam (JURNAL PENELITIAN, 2010)
This research is aimed to described the headmasters of Islamic school’s (Madrasah) views and ideas on the Islamic schools’ future in Indonesia, and explain why and how their views and ideas go on. Based on the thick description of three headmasters of Islamic school, it appears that according to them, the Islamic schools’ future will not only be stronger and more prospective, but also be gloomy. Based on this understanding, it can be developed a hypothesis that Islamic school can develop better under the conditions: (1) get law protection; (2) free from managing dualism of national education; and (3) free from poison of ideology of science dichotomy. Finally, it recommends that other researchers continue this research with wider research, so that it can get generalization to develop formal theory of Islamic school.